Peran Badan Usaha Milik Desa dalam Pemberdayaan Masyarakat Pada Kawasan Pertembangan Emas di Sumbawa Barat - Ibrahim Ibrahim; Ilham Zitri (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2023)
This research examines the role of coastal Village-Owned Enterprises (BUMDes) in community empowerment efforts in gold mining areas in West Sumbawa, Indonesia. Gold mining areas often face challenges related to environmental impacts, social problems and economic inequality. This research aims to understand how BUMDes on the coast contribute to community empowerment, with a focus on the initiatives and programs they have implemented. The method used in this research is qualitative and quantitative descriptive research. The data sources used are primary and secondary data. Data was obtained by means of observation, interviews, and documentation. Data analysis procedures use Data Reduction, Data Display and Drawing Conclusions and Verification. The research results show that BUMDes have a significant role in empowering communities in gold mining areas. They act as managers of local natural resources, such as water and agricultural land, which have a direct impact on the welfare of coastal communities. BUMDes also plays a role in managing mining company funds which are given as a form of compensation to local communities. The results of this research show that BUMDes have great potential to play a more strategic role in mitigating the negative impacts of gold mining and improving the quality of life of communities in coastal areas. However, challenges such as licensing, efficient management and supervision need to be overcome to ensure that BUMDes can operate successfully and provide maximum benefits for coastal communities in West Sumbawa. This research can provide useful insights for stakeholders, local governments and BUMDes in efforts to empower communities in gold mining areas.